2020
DOI: 10.3390/insects11040212
|View full text |Cite
|
Sign up to set email alerts
|

Predation Pressure in Tea (Camellia sinensis) Plantations in Southeastern China Measured by the Sentinel Prey Method

Abstract: Tea (Camellia sinensis) is an important food product with thousands of years of human use. Being a non-washable food, no pesticide residues are allowed, which increases the importance of natural means of plant protection. Predation, a component of natural pest control, is an important contributor to this, but its level and sustainability are not known in most of the areas of tea production. We quantified predation intensity using the artificial sentinel prey method in a tea-growing landscape containing remnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In northern India, four bird species, the Asian-pied Starling (Gracupica contra), Chestnut-tailed Starling (Sturnia malabarica), Jungle Myna (Acridotheres fuscus), and the Red-vented Bulbul (Pycnonotus cafer) are identified as potentially effective biocontrol agents against pest caterpillars [25]. In the studied landscape, we found that birds regularly moved out of the forest fragment, and a concurrent study [29] found an attack rate of 19-25% d −1 on sentinel prey placed on tea plants. The rate of attack increased as the distance to the next forest fragment edge increased.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In northern India, four bird species, the Asian-pied Starling (Gracupica contra), Chestnut-tailed Starling (Sturnia malabarica), Jungle Myna (Acridotheres fuscus), and the Red-vented Bulbul (Pycnonotus cafer) are identified as potentially effective biocontrol agents against pest caterpillars [25]. In the studied landscape, we found that birds regularly moved out of the forest fragment, and a concurrent study [29] found an attack rate of 19-25% d −1 on sentinel prey placed on tea plants. The rate of attack increased as the distance to the next forest fragment edge increased.…”
Section: Discussionmentioning
confidence: 58%
“…In each of the three locations, we selected two forest fragments, and their neighbouring tea gardens. For further details concerning the research sites, see Imboma et al [29].…”
Section: Study Sitesmentioning
confidence: 99%
“…We assessed the predatory activity of carnivorous insects with dummy green caterpillars of moths made of plasticine, exposed for seven days. This method of sentinel prey is easy to use and appropriate to assess in situ predation pressure [39,49]. Dummy caterpillars were 25 mm long and 5 mm in diameter, and made from light green nontoxic modelling plasticine (Fimo Soft ® , Staedtler Mars GmbH & Co. KG, Nuremberg, Germany).…”
Section: Sentinel Preymentioning
confidence: 99%
“…Measuring species interactions such as insect and seed predation is challenging. Instead of measuring the function itself, studies often use densities of predators as a proxy [37], which can be misleading [38,39]. Here, we aimed to study the effects of fragmentation (i.e., increasing isolation, decreasing fragment size, and edge effect) directly on predation in two grassland ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…pest control and pollination, but also disservices, i.e. seed predation (Imboma et al 2020; Morante-Filho and Faria 2017; Wenny et al 2011; Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%